Technology as a didactic tool in the process of children's literacy (Research, Society and Development, 2019)
The present study aims to discuss the use of Information and Communication Technology (ICT) in the pedagogical didactic action of literacy teachers in the 2nd year of elementary school. It initially defends the necessary conformity of the school to modern times, reframing its educational process. The exploratory research describes an investigation carried out with seven literacy teachers from a public school in the city of Fortaleza that aimed to explore their perceptions and expectations regarding the theme. The results show that, for the teacher, articulating the didactic action to the use of technological tools is an acceptable practice that contributes to the dynamism of the class, arousing curiosity in the student while the student appropriates reading and writing in the perspective of literacy. The development of the research revealed obstacles that hindered the systematic implementation of didactic-pedagogical action with the aid of technological tools, because although the idea is in the discourse of legal documents, in the teacher's intention and in the student's interest, scarce public investments do not the application in practice, and refers us to the reflection of what direction the school has taken in the era of modernity.